To your eternity. 18 - Ōima, Yoshitoki (Kodansha Comics, 2022)
A lonely boy wandering the Arctic regions of North America meets a wolf, and the two become fast friends, depending on each other to survive the harsh environment. But the boy has a history, and the wolf is more than meets the eye as well... To Your Eternity is a totally unique and moving manga about death, life, reincarnation, and the nature of love.